Prophetic Communication in the Era of Artificial Intelligence: Efforts to Convey Comprehensive Islamic Messages - Ridwan, Aang (Diroyah : Jurnal Studi Ilmu Hadis, 2023)
The study essentially aims to analyze the changes occurring within the practice of dakwah as a form of communicating Islamic messages in the era of digital technology and artificial intelligence. The practice of dakwah must retain its prophetic communication dimension even as it adjusts to new communication formats brought about by the digital era and artificial intelligence. This study employs a qualitative approach with a descriptive-analytical method. This method was chosen for its capacity to provide a profound understanding of complex phenomena within their contexts, aligned with the research objective to analyze the changes in communication patterns and their effects on dakwah practices. Data is gathered through documentation and observation of dakwah practices across various platforms and digital media. The study indicates that the shifts in dakwah communication patterns in the digital era and the advancement of artificial intelligence have significant and intricate impacts on the comprehensive communication of Islamic prophetic messages. Key points include: (1) Changes in the meaning and practice of dakwah depict a shift in focus from the spiritual and moral aspects to the dissemination of Islamic messages through technological platforms; (2) Changes in dakwah communication formats and platforms reflect the adaptation of preachers to digital trends and audience preferences; (3) The influence of social media in dakwah practices opens broad avenues for disseminating Islamic messages; (4) Artificial intelligence (AI) has notably contributed to presenting dakwah content to the public; (5) Normative dynamics in digital-era dakwah communication reveal the challenges in maintaining a balance between popularity and the integrity of religious teachings; (6) Ethical challenges and controversies in digital dakwah underscore the need to uphold moral and ethical values in religious communication; and (7) Education and supervision emerge as pivotal in addressing the challenges of digital dakwah. Content creators, preachers, and society at large must be equipped with a proper understanding of technology usage aligned with scholarly and ethical responsibility, ensuring that the conveyance of religious messages remains accurate, substantial, and consistent with Islamic values.